Dampak Program Zakat Community Development (ZCD) Di Kelompok Penggemukan Sapi Ternak Mekar Samarinda - Nahdiah Nahdiah; Mursyid Mursyid; Muhammad Nasir (Studia Economica : Jurnal Ekonomi Islam, 2025)
This study aims to trace the impact of the Zakat Community Development (ZCD) program run by BAZNAS East Kalimantan Province using a sustainable livelihood impact assessment (SLIA) which looks at 5 assets, namely natural assets, human assets, financial assets, social assets, and physical assets. This research uses a qualitative method using case studies. The data obtained from this study was through interviews and observations with BAZNAS employees of East Kalimantan Province and the Chairman of the Mekar Cattle Fattening Group as mustahik. The results of this study show that the management and utilization of natural assets in the Mekar Cattle Fattening Group has been carried out well and has an impact on the fertility of the surrounding environment. Likewise, the utilization of human, financial, social, and physical assets has increased from this group after receiving assistance from the zakat community development program, the increase in financial assets can be seen from the increase in cattle sales from this group, and the development of other businesses carried out by the group's members. The social asset is the contribution from the group to the community such as infaq, the contribution of road repairs in their area. The physical assets of this group can also be said to increase with the increase in the number of stables, besides that members of this group can also increase the ownership of personal belongings from the sale of cattle